Determinação da altura de onda solitária a partir da medição de velocidade orbital - de Oliveira Souza, André Luís; de Freitas Maciel, Geraldo (My University, 2006)
The purpose of this experimental work is to investigate solitary wave's characteristics that are generated by impact of granular solid material into water. It was used glass balls to generate the waves. From Boussinesq's classic equations of orbital particle velocity, the wave's amplitude was calculated. The velocity field was measured with ADV (Acoustic Doppler Velocimeter) gauges. A digital camcorder allowed to obtain the wave's amplitude with image analysis. From the movie it was also possible to know the wave pattern. By comparing both wave's amplitudes methods, it was verified the validity and adequately of the horizontal velocity component expression of solitary waves for the range of experiments observed into the water channel.
Determination of the solitary wave's amplitude using orbital velocity measurement